Treatment Outcomes of Carcinoma of the Breast in Pregnancy in Port Harcourt, Nigeria - Elenwo, Solomon N.; Wichendu, Promise N.; Ijah, Rex Friday Ogoronte Alderton (British Journal of Healthcare and Medical Research, 2022)
Background: The belief that breast cancer during pregnancy is more aggressive than in non-pregnant women is still very common in our environment, even amongst medical personnel. Many clinicians still advise women with breast cancer during pregnancy to terminate the pregnancy on prognostic fears. Diagnosis of breast cancer during pregnancy is often delayed due to delayed presentation and some difficulties encountered with imaging during pregnancy. We present the outcomes of management as studied in this center. Materials and Methods: Information was collected from pregnant women who presented to the breast clinic over a 5-year period. The same treatment was given to all of them and the outcomes of treatment analyzed. Results: A total of 31 patients were seen during the period. The patients’ age was between 28years and 39years, with a mean age of 32.5years. Clinical staging showed that 20 patients (64.5%) were Manchester stage II, 9 (29%) stage III, 1 (3.2%) had stage I disease, while only one patient (3.2%) had stage IV disease. Majority of the patients in the study had acceptable outcomes for both the mothers and babies. Conclusion: Pregnancy does not increase the mortality of breast cancer, as some erroneously believe. Accurate timing of chemotherapy and radiotherapy results in no significant harm to the baby. Termination of a desired pregnancy should not be advised unless the woman so desires.